Sosialisasi Pencegahan Infeksi Menular Seksual (IMS) Bagi Remaja Di Sekolah Parulian 3 Medan - Adelina Fitri Tanjung; Eka Ristin Tarigan; Putri Nadila; Merry Lumban Gaol (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Adolescents are an age group that is vulnerable to reproductive health problems, including the risk of Sexually Transmitted Infections (STIs) and risky sexual behaviors, due to limited knowledge and psychosocial maturity. Schools have a strategic role in providing reproductive health education as a promotive and preventive effort. This counseling activity aimed to determine adolescents’ knowledge regarding the prevention of Sexually Transmitted Infections (STIs) among students at Parulian 3 School, Medan.This study employed a one-group pretest–posttest approach. The participants were all seventh-grade students who met the inclusion criteria. The intervention consisted of reproductive health education delivered through lectures, discussions, and visual media. Data were collected using questionnaires measuring knowledge and attitudes before and after the counseling session, and then analyzed descriptively by comparing pretest and posttest results. The results showed an increase in students’ knowledge and attitudes after receiving reproductive health education. The differences in scores before and after the intervention indicate that the counseling provided was effective in improving students’ understanding and fostering positive attitudes toward the prevention of STIs and risky sexual behaviors. Reproductive health education in the school setting is an effective effort to enhance adolescents’ knowledge and attitudes regarding reproductive health. Therefore, reproductive health education activities should be implemented continuously and integrated into school programs.